Presenting the evaluation model of financial technology policies in National Bank of Iran - Vahid moradi; changiz mohammadi zadeh; ali farhadi mahali (ارزش آفرینی در مدیریت کسب و کار)
Abstract The aim of the current research is to provide an evaluation model of financial technology policies in the Melli Bank of Iran. According to its purpose, the research method is applicable-developmental, mixed (qualitative-quantitative) in terms of implementation, and survey-cross-sectional in terms of nature and method. The statistical population of the research in the qualitative part includes 17 experienced managers of Melli Bank of Iran, selected by the purposeful sampling method; and in the quantitative part it includes the managers and experts of the Melli Bank of Iran, with the sample size of 156 people using Cohen's power analysis and using the simple random sampling method. Data collection in the qualitative part was done by semi-structured interviews; and in the quantitative part by the questionnaire. The underlying categories of the research were identified by the grounded theory method and the final model was validated by the partial least squares method. Qualitative data analysis was done with MAXQDA20 software, and the quantitative part was done with Smart PLS. The research findings showed that based on the paradigm model of research; external evaluation, internal evaluation, and evaluation of bank stakeholders have an effect on fintech executive policies. On the other hand, the bank's marketing performance provides background conditions and technology-based risk is also an intervening factor. Finally, the development of fintech and digital banking can be achieved with technological and financial strategies. Also, the GOF index was found to be 0.659, which indicates the good fit of the model. Extended Abstract Introduction The development of fintech has significantly influenced the development of the banking industry. On one hand, the adoption of fintech can lead to technological risks and increase the operational costs of the bank. On the other hand, lack of acceptance of financial technology can threaten banks' competitive ability (Tang et al, 2023). The emergence and development of financial technology has a significant impact on financial institutions, especially commercial banks. Traditional commercial banks are potentially lacking in fintech professional talents and need a detailed policy in this field to use financial technology capabilities. This policy enables commercial banks to have more customers in a larger area (Sarraf & Rahimi, 2022). Fintechs or financial start-ups are influencing more and more areas of the financial services value chain every day. The use of fintechs has provided the rulers of the country's financial markets with an irreplaceable opportunity to reform the mechanisms of the financial system. However, the development of technology in the country's financial system is not easy, and the main factor of this problem is policy making and detailed executive policies (Payandeh & Afghahi, 2023). In the field of banking industry, policy making is more important. Maintaining survival and hope for sustainability in the field of competition due to the technological background has made changes and developments in the policies of the banking system an undeniable necessity. On the other hand, not having a long-term policy and attitude is a concern that exacerbates the uncertainty in the competitive environment for banks (Godarzi et al, 2021). Fintech implementation policies are a critical success factor for using this technology in the banking industry. A detailed evaluation of executive policies ensures the achievement of banks' goals in line with the implementation of financial technology. It has also significantly improved the way customers access financial services, and has brought better financial performance (Allen et al, 2021). Therefore, in this research, we are looking for an answer to this question: what is the evaluation model of financial technology policies in the Melli Bank of Iran? Theoretical Framework fintech Fintech or financial technology refers to a set of businesses that use software and hardware to provide innovative financial services. The National Center for Digital Research in Dublin, Ireland defines fintech as innovation in financial services (Owzaei & Sohrabi, 2017).